Introduction Logic Gates and Digital Systems at SMA 1 Cikarang Pusat - Lukman Medriavin Silalahi; Iksan Bukhori; Mia Galina; Antonius Suhartomo; Erwin Sitompul (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2026)
The rapid development of the Industrial Revolution (IR) 4.0 and the transition towards Society 5.0 demand an increase in digital literacy and a basic understanding of technology systems starting from secondary education. The Community Service (CS) Program conducted by the Department of Electrical Engineering Universitas Presiden aims to introduce the concepts of logic gates and digital systems to students of SMA 1 Cikarang Pusat. This CS integrates theoretical explanations and simulation practice using the online platform Circuitverse. This CS was evaluated using a Likert scale (1–4) questionnaire instrument, namely Expectation (Importance) and Performance, with a total of 40 student respondents. The analysis results show that all indicators received an average performance score above 3.30, with satisfaction indices ranging from 82.50% to 90.62%, which falls into the very high category. The indicator for the use of appropriate technology received the highest score of 90.62%, indicating the relevance of the material to current technological developments. The Importance–Performance Analysis (IPA) shows that most indicators are in the 'maintain performance' quadrant, indicating alignment between participants' expectations and the activity's performance. These findings suggest that the workshop is effective in enhancing students' understanding of basic digital system concepts while also fostering interest in engineering and technology fields. The activity underscores the strategic role of universities in bridging the technology literacy gap at the secondary education level in response to the challenges of the IR4.0 and Society 5.0.